Policy implications of land cover change and carbon dynamics in the Upper Chico River Basin, Cordillera Administrative Region, Philippines - Soriano, Merlyn S.; Tiburan, Cristino L., Jr.; Racelis, Diomedes A.; Peralta, Eleno O. (2020)
An analysis of impacts of land cover change to carbon dynamics and their policy implications was conducted in the Upper Chico River Basin. Landsat imageries from 1988, 2003, and 2016 were processed using Geographic Information System (GIS) and remote sensing software. These software generated a classified map for change analysis. InVEST Carbon Model was utilized to analyze the policy implications of changing regulatory practices in the land cover change and carbon dynamics in the Upper Chico River Basin. Results revealed that from 1988 to 2016, agricultural conversion (0.23 % yr1) and loss of old-growth forest (0.5 % yr1) were the dominant land cover change within the basin despite the implementation of a national policy which banned logging in all natural and residual forests. For the 28-year period, approximately 47%, 9%, and 43% of the basin had stable, sequestered and emitted carbon stocks, respectively. The results suggested the need for updated policy on sustainable forest management in the country to fit the current state of forest resources. This would narrow and bridge the gaps between policy and practice. Regular monitoring and assessment of programs, projects, and policies are therefore indispensable to effectively implement them. Utilization of geospatial technologies and InVEST model should also be considered as its applicability and importance was showcased in this study.
Keywords: Sustainable forestry; Land cover; Sustainable development; Forest management; Carbon sequestration in forests; Policymaking